Mid-latitude Paleogene dinoflagellate cysts from offshore Santa Catarina (Pelotas Basin, Southern Brazil): Taxonomy and biochronostratigraphy - Premaor, Eduardo; Ferreira, Elizabete P.; Souza, Paulo A.; Guerstein, G. Raquel; Arai, Mitsuru [UNESP] (Elsevier, 2021)
Palynological assemblages have been reported in pre-Quaternary deposits of the Pelotas Basin, except in the Santa Catarina Platform, where micropaleontological information is still restricted to calcareous microfossils. The present study documents the taxonomic and biochronostratigraphic analyses of dinoflagellate cysts of 26 cutting samples from well 1-SCS-2, drilled on the northern part of the Pelotas Basin. Palynological assemblages are composed of continental and marine taxa, being dominated by dinoflagellate cysts. A total of 99 taxa, belonging to the orders Gonyaulacales (74 taxa) and Peridiniales (25 taxa), were identified. The main dinoflagellate cysts with biochronostratigraphic value are Hafniasphaera septata, Cerodinium dartmoorium, Membranophoridium perforatum, Cordosphaeridium inodes, Enneadocysta dictyostila, Operculodinium divergens, Corrudinium incompositum, Phthanoperidinium comatum, Phthanoperidinium amoenum and Gelatia inflata. Six palynochronostratigraphic intervals are defined: A (lower to middle Eocene); B (middle to upper Eocene); C (upper Eocene to lower Oligocene); D (lower Oligocene); E (upper Oligocene) and F (upper Oligocene). The integration of the data obtained from dinoflagellate cysts and calcareous nannofossils indicates that the sediments of the Imbé Formation study section were deposited from early to late Eocene (transgressive episode), and those of the Cidreira Formation, during the Oligocene (regressive episode). Biostratigraphic comparisons are displayed, based on the palynological frameworks of Brazilian basins and those of the Northern and Southern Hemisphere. This result allows the correlation of the studied sediments with the intermediate part of the Drift Supersequence in a context of relative sea level rise.
Keywords: Brazilian continental margin; Eocene; Microplankton; Oligocene; Palynology; Palynostratigraphy